Language Choice and Attitude of IKIP Saraswati Students - Desak Nyoman Alit Sudiarthi; I Wayan Mawa; Ni Putu Parmini; I Gede Bagus Wisnu Bayu Temaja (Cita konsultindo, 2023)
IKIP Saraswati is a multicultural campus where people come from various regions and ethnicities and is known as a campus whose advantages include being professional, character and competitive, as well as a campus strategically located in Tabanan. This situation provides excellent opportunities for students to communicate with people from different cultural, ethnic, and linguistic backgrounds. Generally, they speak Balinese, the local language spoken throughout Bali. Meanwhile, because of involvement with those who speak a different language, Bahasa Indonesia is increasingly used. Related to this situation, this research investigated the language choice among students at IKIP Saraswati. This study also examined their language attitudes towards Bahasa Indonesia, daily language, and regional languages in achieving goals. The sociolinguistic questionnaires were administered to 58 sample respondents who were IKIP Saraswati students. The study results showed that students have an appreciative attitude towards the daily language of Bahasa Indonesia, English, and regional languages. An investigation into the choice of language shows that students prefer to communicate using Bahasa Indonesia. The dominance of Bahasa Indonesia shifts the use of regional languages.